Pelatihan Perpajakan Sederhana dan Pencatatan Keuangan pada Umkm Mie Mandangiang untuk Meningkatkan Pemahaman Adminstrasi Usaha - Najwa Kameela Andjani; Kartika Aprilia Putri; Rizki Nurul Aini; Mita Azira; Dwi Fionasari (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service activity aims to improve the understanding of MSME actors regarding basic taxation and financial record-keeping as part of business administration. The activity was conducted on July 15, 2026, at Mie Mandangiang MSME, Jalan Kuau, Pekanbaru City. The methods used included initial observation and interviews, pre-tests, material delivery, discussions and question-and-answer sessions, simple practice, post-tests, and activity evaluation. The results showed that before the training, participants had recorded business income and expenses manually and separated business and personal finances, but their understanding of tax obligations and tax administration was still limited. After participating in the training, participants demonstrated improved understanding of basic taxation, the importance of financial records, the introduction of the Taxpayer Identification Number (NPWP), and the relationship between transaction records and tax obligations. The activity received a positive response from participants and was considered beneficial in improving their understanding and encouraging the implementation of more organized business administration. Therefore, basic taxation and financial record-keeping training can serve as an effort to improve administrative literacy among MSME actors.